2000
DOI: 10.1084/jem.191.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Activation of Natural Killer (Nk) Cells in Vivo Determined by the Target Cell Phenotype

Abstract: Natural killer (NK) cells can spontaneously lyse certain virally infected and transformed cells. However, early in immune responses NK cells are further activated and recruited to tissue sites where they perform effector functions. This process is dependent on cytokines, but it is unclear if it is regulated by NK cell recognition of susceptible target cells. We show here that infiltration of activated NK cells into the peritoneal cavity in response to tumor cells is controlled by the tumor major histocompatibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 63 publications
4
106
0
Order By: Relevance
“…A problem with this interpretation is that it examined only spontaneous NK cell cytolytic activity. Recent studies have shown that the NK cell population in mature mice is nearly devoid of cytolytic activity until activated by stimuli (priming) such as poly(I:C), viral infection, or target cells that express ligands such as Rae1 that stimulate NK cells (40,41). NK cells with spontaneous cytolytic activity are therefore likely to represent only a small subset of the total NK1.1 ϩ CD3 Ϫ population in normal untreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…A problem with this interpretation is that it examined only spontaneous NK cell cytolytic activity. Recent studies have shown that the NK cell population in mature mice is nearly devoid of cytolytic activity until activated by stimuli (priming) such as poly(I:C), viral infection, or target cells that express ligands such as Rae1 that stimulate NK cells (40,41). NK cells with spontaneous cytolytic activity are therefore likely to represent only a small subset of the total NK1.1 ϩ CD3 Ϫ population in normal untreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we explored how NK cells were recruited to a nonlymphoid tissue, with the peritoneal cavity as a model. Studies looking at NK-cell recruitment to this area have been conducted previously, but migration was in those experiments induced by inoculation of tumors or infectious agents [13][14][15]. In the case of tumor inoculation i.p., recruitment was shown to be dependent on TNF [14].…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are found in both nonlymphoid and lymphoid tissues including lung, liver, blood, spleen, and LN [9]. Several studies have demonstrated that NK cells migrate to different tissues in response to stimuli, such as allergic responses, infections, or tumor growth [10][11][12][13][14][15][16][17][18][19]. Four chemokine receptors, CCR2, CCR5, CXCR3 and CX3CR1, have been shown to be particularly important for mouse NK-cell migration to various inflammatory stimulus [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory receptors interacting with MHC selfmolecules interfere with positive signaling, thus protecting normal tissue from NK-cell attack. As predicted by the ''missing self hypothesis'', interaction of NK cells with target cells expressing reduced levels of self MHC, such as virus-infected or tumor cells, ignites the lytic machinery [3][4][5][6]. Inhibitory receptors of mouse NK cells comprise several Ly49 receptors, CD94/NKG2A [7] or CD48 [8].…”
Section: Introductionmentioning
confidence: 99%